Change leader behavior inventory: development and validation of an assessment instrument - Stilwell, Rebecca A.; Shon, DaHee; Pasmore, William A. (2016)
While the pace and complexity of change is increasing, the rate of failed change attempts continues to be unacceptably high. Leaders at every level play a central role in change, yet few receive formal training on how to lead change and to date, a validated assessment to provide feedback on their performance has been lacking. The current study is intended to help close this gap. This article describes an effort to develop and validate an instrument to measure change leadership behaviors, the Change Leader Behavior Inventory. - Reproduced.
Keywords: Leadership; Organizational change